OVERVIEW OF THE NURSE'S KNOWLEDGE ABOUT BUNDLE VENTILATOR ASSOCIATED PNEUMONIAIN INTENSIVE CARE UNIT ROOM PUBLIC HOSPITAL IN THE CITY OF DUMAI (Al Insyirah International Scientific Conference on Health, 2021)
Ventilator Associated Pneumonia (VAP) is Healthcare Associated Infections (HAIs) found in the hospital and it’s a pneumonia infection that occur after 48 hours of mechanical ventilation both endotraceal tubes  and tracheostomy. The risk of nosocomial infection increases  6-21 times throught the use of a ventilator and the mortality rate is 24-70% resulting in an increase in icu admission time and increase in medical cost. Data from the Infection Control Prevention Committee of the Dumai City general hospital in 2018 there were 107 patients on ventilators and  3 patients were experiencing VAP and 50% of nurses did not fully know about the VAP bundle and  all nurses didn’t  received training on the VAP bundle. The type of this study  was a quantitative research with  descriptive design to know the knowledge of nurses about VAP bundle. The research was done on August 2020 in the ICU room of the Dumai City general hospital with a total sampling  20 nurses. The data were collected using a questionnaire sheet about nurses knowledge of the VAP bundle. The results showed that the level of knowledge of nurses about the VAP bundle was 60% having  sufficient knowledge, so the conclucion  is more  ICU nurses having sufficient knowledge about the VAP bundle. knowledge does not always guarantee implementation and compliance, but lack of knowledge can be barrier to nurse implementation and compliance. It is expected to the hospital to provide nursing training based on standardization procedure of the VAP bundle to patients on ventilators and to carry out monitoring and evaluation  such as  nursing audits especially on apply the VAP bundle and implementation a reward and punishment system in order to create nurse discipline in implementation the vap bundle.
Keywords: Knowledge; Nurse; VA bundle; ICU